3D visualization of manufacturing and supply chain using discrete event simulation - Zhou, Hong. (2008)
The discrete even simulation technology has been successfully applied to manufacturing field for many years. People who have benefited from it are coming to require more in terms of efficiency and effectiveness, while manufacturing is facing the challenge of economic globalization. To improve the performance of current discrete event simulaion.